The Grey Area of Religion: Negotiating the Identity of Young Indonesian Muslims Amidst Extremism, Moderatism, and Popular Culture - Waliyuddin, Muhammad Naufal (Tashwirul Afkar, 2024)
This article explores the religious dynamics of the Indonesian young Muslim generation amidst the ongoing dialectical ideological contestation between extremism and moderatism. The article is a literature review of scholarly archive, digital content, and popular culture representations, and then critically analysed. The findings suggest a ‘grey area’ in Indonesian young Muslims’ religious expression; reflecting ambivalent, ambiguous and adaptive performance as part of their psychosocial transition. Instead of totally embracing either the extreme or moderate poles, Indonesian young Muslims construct a fluid, contextualised and often contradictory religiousity. Popular culture and digital media become the main arena in the process of negotiating their religious identity, with digital algorithms helping to systemically shape spiritual experiences as a complex condition that can be categorised as a wicked problem. In the context of youth culture studies, this phenomenon shows the search for new forms of piety that blend with the values of modernity. The uniqueness (novelty) of this research lies in the concept of ‘grey areas of religiosity’ as a new analytical category in contemporary Islamic studies as well as the integration of popular culture and digital technology in understanding the religiosity of Muslim youth, particularly in Indonesia.